Environmental literacy amongyear 5 primary school children in east coast division, Sabah, Malaysia - Wong, Charmaine Andrea; Mohammad Afandi, Syamsul Herman; Ramachandran, Sridar; Shuib, Ahmad; Chan, Jennifer Kim Lian (IDOSI Publications, 2017)
Environmental Literate individuals are those who are able to perceive and interpret the health of the natural environment and take the required action to ensure that the ecosystem is sustained. This is especially crucial in Sabah where the tourism sector relies heavily on its rich natural biodiversity as a source of economic development. This study determined firstly, the level of environmental literacy in terms of ecological knowledge, disposition, competency and pro-environmental behaviour and secondly, the general level of environmental literacy of Year 5 students. A quantitative questionnaire which included four environmental literacy domains, was used to collect data from 1025 Year 5 students from 17 National Primary schools. Interviews with head teachers and observations were carried out to collect data on the general background of each school and its students. Our findings indicate that the Year 5 students have a moderate level of ecological knowledge, a high level of disposition, a low level of competency and a high level of pro-environmental behaviour. Furthermore, the mean EL score of the Year 5 students are at a moderate level. Based on these findings, implications to current educational policy and practice arise including the need to introduce issue identification and action strategy training into formal primary curriculum and involving students with regular hands-on activities with nature.